ANALISIS PENGGUNAAN APLIKASI NIMBUS BM PADA ABSENSI KARYAWAN KEMENPAREKRAF RI BERBASIS ANDROID MENGGUNAKAN METODE TAM - Susanto, Susanto; Surono, Galih (JURNAL ILMIAH INFORMATIKA, 2025)
This study discusses the Nimbus BM application as an Android-based employee attendance solution at the Indonesian Ministry of Tourism and Creative Economy. Attendance is the process of recording the presence and return of individuals in activities, which is important in managing attendance. However, the Nimbus BM application sometimes experiences errors when employees check in and out, especially when the network is unstable, resulting in inaccurate time recording. The simple features of this application are also considered less supportive of optimal attendance needs. This study uses the Technology Acceptance Model (TAM) approach to measure employee acceptance and identify aspects that need to be improved, through four main variables: perceived ease of use, perceived usefulness, attitude towards use, and intention to use. The results of the analysis show that the Nimbus BM application received an average score of 85.09% for all variables, indicating that this application is accepted by the majority of employees. This study is expected to be the basis for further development of the Nimbus BM application, especially in improving features and network stability to be more optimal in meeting employee attendance needs effectively at the Indonesian Ministry of Tourism and Creative Economy.